Degree-Based Topological Indices of Generalized Subdivision Double-Corona Product. (18th January 2022) - Wang, Ying; Waheed, Muhammad; Jamil, Muhammad Kamran; Shah, Syed Mazhar; Aslam, Adnan; Aram, Hamideh
Abstract : Graph operations play an important role in constructing complex network structures from simple graphs. Computation of topological indices of these complex structures via graph products is an important task. In this paper, we generalized the concept of subdivision double-corona product of graphs and investigated the exact expressions of the first and second Zagreb indices, first reformulated Zagreb index, and forgotten topological index (F-index) of this graph operation.